The determinants of health expenditure in Malaysia / Mohd Faiz Jufree - Jufree, Mohd Faiz (Faculty of Business and Management, 2017)
This paper analyzed the determinants of health expenditure in Malaysia. The study used Multiple Linear Regression Model to determined significant relationship between gross domestic product, proportion of population age 65 above, life expectancy, infant mortality and public expenditure towards health expenditure in Malaysia, which covering data for 30 years from 1985 until 2015 which contain 31 observation. The empirical results have found that all of the variables was significant relationship towards health expenditure in Malaysia. This result give additional understanding of the relationship between these independent variables and health expenditure in Malaysia.